Pengaruh Corporate Governance Terhadap Tingkat Kepatuhan Mandatory Disclosure Konvergensi IFRS - Hayyu Atika Sari (Universitas Negeri Padang, 2022)
This study aims to determine the influence of corporate governance on compliance level of Mandatory Disclosure IFRS Convergence. Data obtained from the Indonesia Stock Exchange (IDX) through the website www.idx.co.id in the form of annual reports presented in manufacturing companies in 2020-2021. Pursuant to purposive sampling criterion 150 company used as sample in this research. Hypothesis test in this research using multiple linear regression method. The results showed that the number of members of the board of commissioners has no effect on the compliance level mandatory disclosure IFRS convergence is indicated by the value of regression coefficient of 0.002 with significance of 0.615> α 0.05. Ownership of dispersion has an effect on compliance mandatory disclosure level of IFRS convergence shown by regression coefficient value equal to 0,043 with significance equal to 0,044 <α 0,05. The number of board meetings has no effect on mandatory disclosure level of IFRS convergence indicated by regression coefficient value of 0.002 with significance of 0,558> α 0,05. The number of audit committees has an influence on compliance mandatory disclosure level IFRS convergence is indicated by regression coefficient value of 0.033 with significance of 0.002 <α 0.05.